Movements of the Glandirana Frogs in Japan and South Korea: A Strategy for Defining Geographical Movements of Amphibians - Akira Oike; Koji Tojo; Yoriko Nakamura; Etsuro Ito; Masahisa Nakamura (International Journal of Zoology)
The Japanese islands were originally included in the Eurasian Continent as part of the southern and northern landmasses. The two landmasses were detached from the continent 18 million years ago. After that, the former was repeatedly connected to the Korean peninsula during glacial periods, but most of the latter was under seawater. Thus, all Japanese amphibians are undoubtedly derived from this nearby continent. However, it is unclear where the amphibians moved during the formation of the Japanese islands. To address the issue, we selected Glandirana rugosa as a representative of Japanese amphibians because this frog is the only species among amphibians in which nucleotide sequences of the mitochondrial genes and sex chromosome evolution have been deeply investigated. Then, we constructed time-calibrated and RAxML phylogenetic trees based on nucleotide sequences of the mitochondrial genes of the Glandirana frogs in Japan and South Korea. Various sites were used to select SNP data from the Glandirana species and their sex chromosome evolution, and the cladograms we obtained suggest that ancient Glandirana frogs except for one group moved along with the southern landmass, when it was separated from the continent. The movements of the Glandirana frogs in Japan and South Korea obtained as results of this study will help scientists to understand the geographical changes that took place during the formation of the Japanese islands. This strategy is applicable to studying and understanding the movements of other amphibian species of the Eurasian and other continents.